2021
DOI: 10.1186/s40709-021-00138-5
|View full text |Cite
|
Sign up to set email alerts
|

Barley somatic embryogenesis-an attempt to modify variation induced in tissue culture

Abstract: Background Somatic embryogenesis is a phenomenon carried out in an environment that generates abiotic stress. Thus, regenerants may differ from the source of explants at the morphological, genetic, and epigenetic levels. The DNA changes may be the outcome of induction media ingredients (i.e., copper and silver ions) and their concentrations and time of in vitro cultures. Results This study optimised the level of copper and silver ion concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 93 publications
0
9
2
Order By: Relevance
“…Then, it is not evident whether such results should be interpreted concerning methylation of the mobile elements or their mobility. On the other hand, the level of methylation (and sequence) changes evaluated in the study is only slightly higher than that for the same species using metAFLP alone [76,119,120]. Assuming MSTD amplifies short fragments (the range is 45-500 bp [121]), our results may, at least partly, reflect mobile elements' movement due to methylation changes due to microspore reprogramming.…”
Section: Discussioncontrasting
confidence: 53%
“…Then, it is not evident whether such results should be interpreted concerning methylation of the mobile elements or their mobility. On the other hand, the level of methylation (and sequence) changes evaluated in the study is only slightly higher than that for the same species using metAFLP alone [76,119,120]. Assuming MSTD amplifies short fragments (the range is 45-500 bp [121]), our results may, at least partly, reflect mobile elements' movement due to methylation changes due to microspore reprogramming.…”
Section: Discussioncontrasting
confidence: 53%
“…However, the TCIV and SV terms are often used mutually [7]. TCIV may be pronounced at the morphological [8], biochemical [9], genetic [10] and epigenetic [11] levels, which do not necessarily overlap [12]. Possibly the most investigated level is based on DNA markers.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, another AFLP based technique, the so-called methylation sensitive AFLP (metAFLP) approach, was developed [ 1 , 39 ], allowing quantification of sequence and DNA methylation changes during a single experiment. Further advances in the technique showed that one might study not only CG and CHG but also the CHH methylation context, an essential tool in studies on cereals [ 1 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations